Ethiopia Economic Update : The Inescapable Manufacturing-Services Nexus - World Bank (World Bank, Washington, DC, 2018)
Ethiopia’s gross domestic product (GDP) growth is estimated to have rebounded to 10.9 percent in FY2017. According to official statistics, Ethiopia’s annual rate of economic growth, which averaged 10.3 percent over 2005/06-2015/16 (compared with the regional average of 5.4 percent), slowed to 8 percent in FY2016 due to drought-related lower agricultural production. With agricultural recovery, gross domestic product (GDP) growth rebounded in FY2017. The pursuit of prudent fiscal policy, with a fiscal deficit at 3.4 percent of GDP, should help keep inflation under control, providing monetary conditions remain tight in the aftermath of the devaluation of the Birr in October 2017. Key challenges relate to poor export performance (Ethiopia’s growth has been driven by investment followed by private consumption) and weak trade balance, which reflect the lack of external competitiveness and the vulnerability to terms of-trade shocks. The rising risk of external debt distress may affect Ethiopia’s access to external finance. These developments require continued policy adjustment to crowd-in the private sector and strengthen Ethiopia’s competitiveness. Part one of this Economic Update, on recent economic developments and outlook, discusses Ethiopia’s growth strategy, emphasizing the sustainability of the country’s investment-focused and export-led growth model. Part two looks at the interlinkages between manufacturing and services, with a special focus on the role of distribution services in promoting Ethiopia’s export competitiveness and eventually its structural transformation.